2010
DOI: 10.1158/1535-7163.mct-10-0548
|View full text |Cite
|
Sign up to set email alerts
|

SCH 2047069, a Novel Oral Kinesin Spindle Protein Inhibitor, Shows Single-Agent Antitumor Activity and Enhances the Efficacy of Chemotherapeutics

Abstract: Kinesin spindle protein (KSP) is a mitotic kinesin required for the formation of the bipolar mitotic spindle, and inhibition of this motor protein results in mitotic arrest and cell death. KSP inhibitors show preclinical antitumor activity and are currently undergoing testing in clinical trials. These agents have been dosed intravenously using various dosing schedules. We sought to identify a KSP inhibitor that could be delivered orally and thus provide convenience of dosing as well as the ability to achieve m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…The anticancer mechanism of vincristine is binding to tubulin dimers and inhibiting the assembly of the microtubule structures, which leads to mitotic arrest in the metaphase 78. The thiadiazole derivative SCH2047069, used as a KSP inhibitor, exhibited potent antitumor activity against leukemia, lymphoma, ovarian, and colon tumors, both in vitro and in vivo 36. In A2780 tumor cell lines, SCH2047069 dosed orally weekly at 10 mg kg −1 only resulted in 41 % tumor growth inhibition (TGI) 36.…”
Section: Ksp Inhibitors In Combination With Chemotherapeutic Agentsmentioning
confidence: 99%
See 3 more Smart Citations
“…The anticancer mechanism of vincristine is binding to tubulin dimers and inhibiting the assembly of the microtubule structures, which leads to mitotic arrest in the metaphase 78. The thiadiazole derivative SCH2047069, used as a KSP inhibitor, exhibited potent antitumor activity against leukemia, lymphoma, ovarian, and colon tumors, both in vitro and in vivo 36. In A2780 tumor cell lines, SCH2047069 dosed orally weekly at 10 mg kg −1 only resulted in 41 % tumor growth inhibition (TGI) 36.…”
Section: Ksp Inhibitors In Combination With Chemotherapeutic Agentsmentioning
confidence: 99%
“…The thiadiazole derivative SCH2047069, used as a KSP inhibitor, exhibited potent antitumor activity against leukemia, lymphoma, ovarian, and colon tumors, both in vitro and in vivo 36. In A2780 tumor cell lines, SCH2047069 dosed orally weekly at 10 mg kg −1 only resulted in 41 % tumor growth inhibition (TGI) 36. Conversely, the trial investigating the effects of combining SCH2047069 with vincristine demonstrated a significant enhancement of activity (76 % TGI).…”
Section: Ksp Inhibitors In Combination With Chemotherapeutic Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…First evidence that kinesin inhibition might be explored as a new anti-cancer strategy came in 2004 [10] and chemical inhibitors of Eg5 have been designed and tested with success against solid tumors in preclinical tumor models [11]. Consequently, there are increasing numbers of clinical trials investigating the efficacy of Eg5 inhibitors alone or associated with classical chemotherapy in hematological and solid malignancies [12].…”
Section: Introductionmentioning
confidence: 99%